A field guide for Arctic oil spill behavior - Schulze, Robert H.; United States. Coast Guard. Office of Research and Development.; U.S. Coast Guard Research & Development Center.; Arctec Incorporated. (Washington, D.C. : U.S. Department of Transportation, United States Coast Guard, Office of Research and Development, 1984)
"November 1984." Prepared for U.S. Coast Guard Research and Development Center. Cover title. Includes bibliographical references. Final report. Mode of access: Internet.